Solving the Equation: (9 × 4) ÷ 6 + 3 ÷ 3 = ?
Let's break down the equation stepbystep to find the solution.
Order of Operations: PEMDAS/BODMAS
Remember the order of operations:
 Parentheses ( Brackets)
 Exponents ( Orders)
 Multiplication and Division (from left to right)
 Addition and Subtraction (from left to right)
Solving the Equation:

(9 × 4) ÷ 6 + 3 ÷ 3
 We start with the parentheses: 9 × 4 = 36
 Now we have: 36 ÷ 6 + 3 ÷ 3

36 ÷ 6 + 3 ÷ 3
 Perform the divisions from left to right: 36 ÷ 6 = 6 and 3 ÷ 3 = 1
 Now we have: 6 + 1

6 + 1
 Finally, we add: 6 + 1 = 7
The Solution
Therefore, the solution to the equation (9 × 4) ÷ 6 + 3 ÷ 3 = 7.